2019
DOI: 10.1016/j.maturitas.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Italian Association of Sleep Medicine (AIMS) position statement and guideline on the treatment of menopausal sleep disorders

Abstract: Insomnia, vasomotor symptoms (VMS) and depression often co-occur after the menopause, with consequent health problems and reductions in quality of life. The aim of this position statement is to provide evidence-based advice on the management of postmenopausal sleep disorders derived from a systematic review of the literature. The latter yielded results on VMS, insomnia, circadian rhythm disorders, obstructive sleep apnea (OSA) and restless leg syndrome (RLS). Overall, the studies show that menopausal hormone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 67 publications
0
18
0
1
Order By: Relevance
“…It has also been reported that central serotonin plays an important role in the regulation of circadian rhythm by modulating the activity of SCN neurons [25], and estrogen enhances the dorsal raphe serotonin system response to environmental light exposure [26]. Furthermore, SSRIs reportedly improve sleep disorder in postmenopausal women, suggesting that the serotonergic system is possibly involved in the circadian rhythm regulation by estrogen [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been reported that central serotonin plays an important role in the regulation of circadian rhythm by modulating the activity of SCN neurons [25], and estrogen enhances the dorsal raphe serotonin system response to environmental light exposure [26]. Furthermore, SSRIs reportedly improve sleep disorder in postmenopausal women, suggesting that the serotonergic system is possibly involved in the circadian rhythm regulation by estrogen [5].…”
Section: Introductionmentioning
confidence: 98%
“…Estrogen plays an important role in the regulation of energy homeostasis in women [1]. The marked decrease in systemic estrogen levels after menopause often causes weight gain, obesity, or sleep disorder, which are serious public health concerns in modern society [2][3][4][5]. A large number of studies have demonstrated that estrogen reduces energy intake by affecting the activity of hypothalamic neurons that regulate food intake [1,6,7], however the mechanism has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Isso porque atividades físicas regulares aumentam a densidade mineral óssea, o VO 2 máximo, a força muscular e o equilíbrio, repercutindo positivamente na composição corporal (CAPUTO;SEIDELEN et al, 2017). Quanto aos fatores clínicos, melhora o sistema imunológico, promove efeitos anti-inflamatórios (ZBINDEN-FONCEA et al, 2020), reduz o risco de resistência à insulina, diabetes tipo 2, síndrome metabólica e risco de doenças cardiovasculares (STERNFELD; DUGAN, 2011;COLBERG et al, 2016;BIRD;HAWLEY, 2017;SYLOW;RITCHER, 2019), além de reduzir os sintomas vasomotores (SILVESTRI et al, 2019) e sintomas psicológicos (SILVESTRI et al, 2019;SPÖRNDLY-NEES et al, 2017;MORARDPOUR et al, 2020), sintomas recorrentes nesse período (MOILANEN et al, 2012).…”
Section: Climatériounclassified
“…The Italian Association of Sleep Medicine (2019) carried out a systematic review of evidence informing a position statement on the management of postmenopausal sleep disorders. 25 This emphasises the co-occurrence of insomnia, vasomotor symptoms and depression. It states that overall hormone replacement therapy (HRT) improves vasomotor symptoms, insomnia and mood, and that postmenopausal insomnia is best managed with HRT and CBT-I.…”
Section: Introductionmentioning
confidence: 99%
“…The BAP advises antidepressants should be considered when there is a co-existent mood disorder. 25 However, the side effect profile of commonly used SSRIs can lead to counter-productive sleep disruption and sexual dysfunction. 42 Sedating drugs (trazodone or mirtazapine) have been shown to reduce insomnia in people with depression.…”
Section: Introductionmentioning
confidence: 99%